Synthesis, characterization, and electrical and optical properties of magnesium-type boracite - Ibroska, Tugba; Kipcak, Azmi Seyhun; Aydin Yuksel, Sureyya; Derun, Emek; Piskin, Sabriye (Tubitak Scientific & Technological Research Council Turkey, 2015)
Synthesis of the magnesium type of the mineral boracite (Mg3B7O13Cl) was studied. Several parameters affecting boracite synthesis were investigated. The raw materials selected were magnesium chloride hexahydrate (MgCl2 center dot 6H(2)O), magnesium oxide (MgO), and boron oxide (B2O3). Reaction temperatures were selected between 600 degrees C and 900 degrees C. Moreover, three different reaction times of 4, 1, and 0.5 h were studied with the determined optimum molar ratio, reaction temperature, and reaction medium. Synthesized boracite characterization analyses were done by the techniques of X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and scanning electron microscope (SEM). Reaction yields were also calculated. From the results of this study the magnesium type of boracite was obtained as a single phase with high XRD crystal score. Optimum conditions for the synthesis were as follows: MgCl2 center dot 6H(2)O to B2O3 mole ratios of 5:6.5, 5:7.5, 6:6.5, 6:7.5, 7:6.5, 7:7.5; 600 degrees C reaction temperature; 1 h reaction time; and reaction medium as air atmosphere. Reaction yields were between 58.81 +/- 1.65% and 77.49 +/- 1.86%. Some selected magnesium type of boracite minerals, electrical resistivity, and optical absorbance properties were also measured for the determination of physical properties.
Keywords: Magnesium-type boracite; solid-state synthesis; reaction yield; BORATE MG2B2O5 NANOWIRES; GROWTH; ROUTE; FE; Chemistry; Engineering